PERTUMBUHAN BIBIT MANGROVE (Rhizopora sp.) PADA MEDIUM HIDRAQUENT YANG DIBERI BEBERAPA DOSIS NPK - Trisnawati Trisnawati; Wardati Wardati; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the effect of giving some doses of NPK fertilizer and get the best dose on the growth of mangrove seedlings (Rhizopora sp.). This research was conducted in Bantan Tengah Village, Bantan District, Bengkalis Regency, Riau Province. This research was conducted for 3 months starting from February to April 2015. This experiment was conducted experimentally based on Randomized Complete Design (RAL) with 5 treatments, and 4 replications so that there were 20 experimental units, each experimental unit consisted of 3 seeds. The treatment was the doses NPK fertilizer that consist : T0 = Without NPK, T1 = 3 grams NPK, T2 = 6 grams NPK, T3 = 9 grams NPK, T4 = 12 grams NPK. Parameters observed were height of seedlings, number of leaves, root volume, dry weight of seedlings and shootroot ratio. The results showed that the dosage of 12 gram showed its effect on the parameters of plant height increase, number of leaves, root volume, root canopy ratio and dry weight of seedlings. Giving with a dose of 12 grams /10 kg medium is the best dose to increase the growth of mangrove (Rhizopora sp.). Keywords: Mangrove (Rhizopora sp). And NPK fertilizer